On-body radio propagation channel characterization at 2.45 GHz and its exposure effects on neurophysiological and behavioral of adults - Hasliza, A. Rahim@Samsuddin
The emergence of Body-centric Wireless Communication (BCWC) integrated with textile-based antenna in various applications has open door to a new dimension of ergonomic body-worn communications. In such environmental settings, human body characteristics with different dimensions and tissue properties, and dynamic movements of the body are the major factors in influencing the on-body radio propagation channel characteristics. The presence of metallic objects worn on their bodies, such as spectacles, watches, belt-buckles, and jewelry is another concern that may affect the operability of BCWC in terms of reliability and efficiency of the communication link. Additionally, due to the nature of human body that involves in various movements makes this radio channel more difficult to be characterized coupled with the presence of metallic accessories. Thus, a thorough experimental investigation of the influence of onbody worn metallic items on the on-body propagation channel considering static and dynamic body motion is required in further facilitating a reliable wireless communication link. The thesis focuses on the characterization of the narrowband (2.45 GHz) on-body radio propagation channel considering metallic accessories, i.e., spectacles and watches by utilizing wearable textile monopole antennas. The path loss of the on-body radio channel is characterized explicitly taking into account the body size of the subjects. The results show that the path loss exponent tends to be lower for full-rimmed spectacles for normal subjects compared to underweight and overweight subjects, by 1.4% in static scenario. For metallic loop-like accessories, the results indicate that for normal subjects, there is more influence in path loss exponent value, up to 11.4%, compared to underweight and overweight subjects. Furthermore, our finding indicated that there was statistical significant difference between with and without metallic watch (tungsten) towards subject specificity effects for both body and arm movements at several on-body links which were closer to the metallic watch (P<0.05, ANOVA test). The path loss decreases when the reception terminal is positioned very close to the metallic loop-like accessories. If such loop-like metallic accessory along with subject specificity is not being appropriately considered when designing the radio channel, a reliable body-centric wireless system may be degraded. The investigations are extended further to study the possible effect of 2.45 GHz wireless body area network radio frequency (WBAN RF) radiation on the neurophysiological (electroencephalogram (EEG)), cognitive performance, well-being and physiological parameters of adults, emitted by wearable planar textile antenna. The results demonstrate that there is no statistically significant difference between the active exposure and Sham exposure on EEG, cognitive performance, well-being, and physiological parameters effects (P‘s>0.05). In addition, the effects of WBAN exposure are experimentally investigated in relation to different antennas topologies. The results reveal that there is significant resting EEG power alteration in frontal and temporal regions when exposed to short-term textile patch radiation compared to textile monopole radiation between left and right hemispheres of the brain (P<0.001). However, there is no statistically significant difference between textile patch and textile monopole exposures on well-being, body temperature, blood pressure, and heart rate of adults (P‘s>0.05). This research has led to a better understanding of static and dynamic on-body propagation channels of the effects of metallic accessories on subject specificity as well as its exposure effects on the neurophysiological and behavioral of adults.